2020
DOI: 10.3171/2019.6.spine181099
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation failure: evaluation of factors underlying hardware explantation

Abstract: OBJECTIVESpinal cord stimulation has been shown to improve pain relief and reduce narcotic analgesic use in cases of complex refractory pain syndromes. However, a subset of patients ultimately undergoes removal of the spinal cord stimulator (SCS) system, presumably because of surgical complications or poor efficacy. This retrospective study addresses the paucity of evidence regarding risk factors and underlying causes of spinal cord stimulation failures that necessita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…If present, anxiety and depression were the most common. Patel et al demonstrated a correlation between SCS failure and certain psychiatric disorders, including PTSD, depression, and anxiety that resulted in system removal (30). All of our patients underwent preoperative psychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…If present, anxiety and depression were the most common. Patel et al demonstrated a correlation between SCS failure and certain psychiatric disorders, including PTSD, depression, and anxiety that resulted in system removal (30). All of our patients underwent preoperative psychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…If this is the case, SCS system explantation is often performed and a substantial proportion of these explants happens before 2.25 years of SCS treatment [63], the so-called "break even" point for SCS treatment when compared with conventional medical management [64]. Patel et al (2019) reviewed the reasons for SCS device explantation in a sample of 129 patients who were treated with SCS [65]. The median time to explantation was 20 months (IQR 7.5-45.5 months), with the primary reason being a lack of efficacy (80.6%) [65].…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al (2019) reviewed the reasons for SCS device explantation in a sample of 129 patients who were treated with SCS [65]. The median time to explantation was 20 months (IQR 7.5-45.5 months), with the primary reason being a lack of efficacy (80.6%) [65]. Only patients who had not yet undergone a device explantation were eligible in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Infection is an inherent risk with any invasive procedure, particularly when a foreign body is implanted; it occurred in 2.45–5% of cases in large SCS series and meta‐analyses and in up to 14% in small series . Infection is the most common acute postsurgical SCS complication leading to removal of SCS equipment and, as removal is generally followed by replacement of the entire system, is one of the more costly complications.…”
Section: Discussionmentioning
confidence: 99%